Childhood corneal blindness: a retrospective study in a tertiary eye hospital of eastern region of Nepal - Panjiyar, Paras; Gautam, Vijay; Rai, Pooja Gautam; Puri, Lila Raj (Nepalese Journal of Ophthalmology, 2016)
Introduction: Studies from Nepal show that most of the cases of unilateral childhood blindness are due to corneal causes. It was also observed that these corneal causes were mostly preventable or treatable. Objective: to study the patterns of corneal diseases in a pediatric out-patient department of a hospital in the eastern region of Nepal. Methods: A retrospective study of the patients who presented to the pediatric department of our hospital in the year 2014 was done with the help of the data received from the hospital recording system. Detail examination of every case was done in the out-patient-department of the hospital by pediatric ophthalmologists. Patients with only corneal disease were included, and those with corneal disease along with other ocular disease were excluded from the study. Results: Of 20,250 patients examined in the pediatric department over a one year period, 1911(9.4%) presented with isolated corneal problems. Keratitis and corneal ulcer were found in 47.8% of them. Corneal trauma was present in 5.6% and vitamin A deficiency leading to corneal opacity and keratomalacia was seen in 0.06% of the cases. Corneal blindness was observed in 66 eyes (bilateral in 3 cases). No case of trachoma or congenital corneal disease was observed. Conclusion: Childhood corneal blindness is mostly due to preventable and treatable causes. Nepal J Ophthalmol 2016; 8(15): 18-22